Trinity, revelation, and reading: a theological introduction to the Bible and its interpretation - Swain, Scott R. ca. 20./21. Jh. (T&T Clark International, 2011)
The Trinity, the kingdom, and the historical progression of the Word of God -- The role of Holy Scripture in kingdom and covenant -- The inspiration and perfection of Holy Scripture -- Reading as an act of covenant mutuality, part one : regeneration, renewal, and the role of the church -- Reading as an act of covenant mutuality, part two : the practice of reading and the shape of interpretation.